2015
DOI: 10.1111/ajt.13245
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Organ Trafficking Networks: A Survey-Based Plea to Breach the Secrecy Oath

Abstract: Patients travel worldwide to purchase kidneys. Transplant professionals can play a role in identifying kidney purchase. However, due to the tension between their rights and obligations, a lack of understanding and knowledge exists on how to prevent and report purchase. We present the results of a national survey that describes transplant professionals' experiences, attitudes, behaviors, conflicts of duties, legal knowledge and needs for guidelines toward patients who purchase kidneys abroad. Second, we clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Of the 76 articles that present patients who traveled, 42 articles describe them as “transplant tourists” who “bought” organs by undergoing “commercial” , “self‐sponsored” , or “paid” transplantations abroad (Table ). Together, these articles report 2921 “tourists” (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 76 articles that present patients who traveled, 42 articles describe them as “transplant tourists” who “bought” organs by undergoing “commercial” , “self‐sponsored” , or “paid” transplantations abroad (Table ). Together, these articles report 2921 “tourists” (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, what is needed is not only more rigorous quantitative and qualitative studies but also efforts to integrate available information. First, national surveys could be circulated among transplant professionals to document domestic cases of organ purchase . Second, transplant professionals could contribute to gaps in knowledge by conducting anonymous interviews with patients about their motivations and experiences with undergoing commercial transplants abroad .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We interviewed 41 transplant professionals based in hospitals throughout The Netherlands, most of whom completed our survey and who reported having treated patients whom they suspected or knew had purchased kidneys abroad (Ambagtsheer et al, 2015). The respondents comprised 29 nephrologists (N), 5 nurse practitioners (NP), 5 social workers (SW), 1 research nurse and 1 transplant surgeon.…”
Section: Methodsmentioning
confidence: 99%
“…Various commentators have suggested that requiring the reporting of this information, for example to a central public health authority, would help to combat transplant tourism by providing information about the nature and scope of the phenomenon and would potentially facilitate follow-up by regulators in the relevant jurisdiction. 6,9,10 The potential merits of such a reporting scheme present an opportunity for modest, yet valuable, legal reform in Canada. Existing health information legislation could be amended to create a reporting system that permits or even requires physicians to provide basic information about suspected transplant tourism, including the location and any known details about the organ transplant network.…”
Section: Key Pointsmentioning
confidence: 99%